Environmens study for determentation the concentration and origin of Hydrocarbon in sediment cores of Al-Azim - Al-Taae, E. O.; Al-Bethani, A. H.; Al-Saad, T. H. (Iraqi Journal of Aquaculture, 2022)
The present study appear the concentration, source and origin of petroleum hydrocarbons in sediment core of two station of Hor Al- Azim at Hor Al – Huwaiza ,total hydrocarbon measurement by spectroflurometer were in these sediment cores. Higher concentration (20.5 μg/g) dry weight at depthe (0-5) cm in Azim (I) while lower conceatrations (1.5) μg/g dry weight at depth (100-105) cm, in Al-Azim (II) higher conceantration was (17.52) μg/g at (0-5) cm depth and lower concentration (1.73) μg/g at depth (80 -85) cm .The higher percentage for total organic carbon (TOC%) appear in Al-Azim (I) (3.52)% at depth (0-5) cm while lower percentage were (0.15)% at depth (90-95) cm . In Al-Azim (II) higher percentage were (4.2)% at depth (0-5) while lower percentage (0.72)% at depth (80-85) cm and we well do to analysis grain size at the sediment were mainly muddy silt with low sand in addition to ports sheel from mollusca shell and disintegrate vegetation for both of the tow core.